Conjugate heat transfer investigation of core damage propagation during total instantaneous blockage in SFR fuel subassembly. (April 2016) - Ravi, L.; Velusamy, K.; Chellapandi, P.
Highlights: Conjugate 2-D thermal model for total blockage in fuel subassembly is proposed. Initiation and propagation of sodium voiding and clad/fuel melting are predicted. Influence of natural convection in fuel pool on damage progression is assessed. Blockage detection through core monitoring thermocouple is ensured. Thermal load on core catcher is quantified. Abstract: Total instantaneous blockage at the inlet of a fuel subassembly (SA) is considered as a beyond design basis event in sodium cooled fast reactors. It is the bounding case of various types of local blockages and to cater for this event, a core catcher is provided at the bottom of the core. The extent of core damage propagation, before reactor trips, forms an important input for thermal design of the core catcher. Neutronics of the core is influenced by various phenomena that take place within the blocked SA, viz., (i) sodium boiling and clad/fuel melting, (ii) location within the blocked SA where these phenomena initiate and (iii) their rate of propagation inside the SA. Reactor trip by core temperature monitoring system of the neighboring SA is affected by (i) heat transfer between the molten fuel pool and the neighboring SA, (ii) number of fuel pins in the SA, (iii) rate of melting of the hexcan and (iv) thermocouple time constant. Towards understanding the thermal hydraulics of damage propagation, a coupled 2-dimensional transient thermal hydraulic model has been proposed. The model considers explicit representation of all the rows of fuel pins within the blocked SA and axial power distribution in the pins. For a realistic estimate of heat flux on the neighboring SA hexcan, natural convection in the heat generating molten fuel pool is considered. The damage propagation to the hexcan is determined by an enthalpy based energy equation, to model moving interface with melting/solidification. The models for turbulent natural convection in the fuel pool, and thermocouple response of neighboring SA are validated against published data in open literature. By detailed parametric studies, it is established that the damage is restricted to seven SA, in the event of TIB for a medium size fast reactor. The proposed 2-D model predicts a faster damage propagation than the 1-D models. However, residual thickness of the hexcan at the time reactor trip is 51%, which is nearly same as that predicted by the 1-D model. Thermocouple time constant is found to be a sensitive parameter for early detection of the TIB. When the number of pins in a SA is reduced, the residual thickness of the neighboring SA hexcan increases.